How do risk attitudes affect measured confidence? - Zahra Murad; Martin Sefton; Chris Starmer (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2014)
We examine the relationship between confidence in own absolute performance and risk attitudes using two elicitation procedures: self-reported (non-incentivised) confidence and an incentivised procedure that elicits the certainty equivalent of a bet based on performance. The former procedure reproduces the "hard-easy effect" (overconfidence in easy tasks and underconfidence in hard tasks) found in a large number of studies using non-incentivised self-reports. The latter procedure produces general underconfidence, which is significantly reduced, but not eliminated when we filter out the effects of risk attitudes. Finally, we find that self-reported confidence correlates significantly with features of individual risk attitudes including parameters of individual probability weighting.
Keywords: C91; D81; 330; Overconfidence; Underconfidence; Experiment; Risk Preferences